Decolonizing the criminal question - Aliverti, Ana (Punishment & society, 2021)
In the last years there has been a growing effort from different theoretical perspectives to interrogate critically the impact of colonialism in the past and present of institutions and practices of crime control, both at the central and peripheral contexts, as well as in the production of knowledge in the criminological field. In this feature piece we examine this debate. We offer a critical account of key themes and problems that emerge from the intimate relationship between colonialism and punishment that directly challenge the persistent neglect of these dimensions in mainstream criminological scholarship. We aim to foreground the relevance of this relationship to contemporary enquiries. We highlight that decolonization did not dismantle the colonial roots of the cultural, social and political mechanisms informing contemporary punishment. They are still very much part of criminal justice practice and are thus also central to criminological knowledge productions.